DECONSTRUCTING THE AMERICAN DREAM IN THE CHINESE-AMERICAN NARRATIVE OF REBECCA F. KUANG'S NOVELS - Akbar, Rifqi; Adi, Ida Rochani (Rubikon : Journal of Transnational American Studies, 2026)
The American Dream as the axis of diaspora pathways has an impact on the construction of American diaspora novels, especially the perspective of Chinese-American female writers, one of whom is RF Kuang. This study focuses on RF Kuang's reflection in representing the American Dream. For the American diaspora, this dream still marginalizes the existence of minorities and is exclusive to white people. Diaspora writers always conflict with ambivalent values that must intersect with the American Dream so that this racism can be dissolved in American society and achieve equality. Through Derrida, American diaspora writers are given a third space to implement the American dream and ideological contestation that provides a nuance of transnational solidarity. This dream is conveyed through Kuang’s novels Poppy War Trilogy: An Arcane of History: Babel; and Yellowface. This research indicates that each of Kuang’s works is constructed within the myth as the foreground, and it is negotiated through her achievements, exclusivity, and inclusivity in literary production, the equality in the characterization, and the Chinese Dream, which forms the contestation. These elements represent the Chinese-American narrative, as well as the existence of the Asian-American diaspora within the American publishing system, which significantly pulls in a global popularity among international audiences.